CITY BRANDING AND THE TOURIST GAZE: PENGEMBANGAN WISATA KOTA - Siregar, Afrila Mulyati Siregar; Suharyono, Suharyono; Kusumawati, Andriani (FIA UB, 2020)
The purpose of this study is to present the conceptual framework of city branding that combines it with the concept of tourist gaze as a tourist perspective which makes it a framework for attracting tourists, investors and new residents, especially in city tourism. This study explores the essence of city branding that is linked to urban tourism through the theory of